Investigating the Effect of Different Concentrations of Murashige and Skoog (MS) Medium and Sucrose on the Production of Potato (Solanum tuberosum L.) Microtubers in vitro - F. Yarmohammadi; A. Motallebi-Azar; S. Kazemiani; Mina Amani (Majallah-i ̒Ulum-i Bāghbānī, 2024)
Introduction Considering the sensitivity of potatoes (Solanum tuberosum L.) to viruses, the production of virus-free plants through in vitro cultivation and their propagation leads to a reduction in costs and an increase in yield. One of the effective methods of reducing plant diseases and producing disease-free microtubers is the use of in-vitro production methods. Considering the role and importance of macro elements and micro elements in the growth of microtubers, it is possible to change the composition of MS culture medium by changing the concentration of salts of macro elements and micro elements without disturbing the balance of elements. This experiment aims to investigate the effect of different concentrations of macro elements (2 Mac, Mac, ½ Mac) and micro elements (2 Mic, Mic, ½ Mic) of MS culture medium in combination with two concentrations of sucrose (80 and 160 g.l-1) was performed on in vitro micronodulation of Agria potato.